Determination of bisphenol A in thermal printing papers treated by alkaline aqueous solution using the combination of single‐drop microextraction and HPLC. Issue 7 (8th March 2013) - Gao, Leihong; Zou, Jing; Liu, Haihong; Zeng, Jingbin; Wang, Yiru; Chen, Xi
<x xml:space="preserve">Abstract</x> A method for the quantitative determination of bisphenol A in thermal printing paper was developed and validated. Bisphenol A was extracted from the paper samples using 2% NaOH solution, then the extracted analyte was enriched using single‐drop microextraction followed by HPLC analysis. Several parameters relating to the single‐drop microextraction efficiency including extraction solvent, extraction temperature and time, stirring rate, and pH of donor phase were studied and optimized. Spiked recovery of bisphenol A at 20 and 5 mg/g was found to be 95.8 and 108%, and the method detection limit and method quantification limit was 0.03 and 0.01 mg/g, respectively. Under the optimized conditions, the proposed method was applied to the determination of bisphenol A in seven types of thermal printing paper samples, and the concentration of bisphenol A was found in the range of 0.53–20.9 mg/g. The considerably minimum usage of organic solvents (5 μL 1‐octanol) and high enrichment factor (189–197) in the sample preparation are the two highlighted advantages in comparison with previously published works.